Prevalensi Status Gizi Pendek pada Anak Sekolah dan Pendapatan Keluarga - M. Anas Anasiru (Jurnal Kesehatan Manarang, 2019)
Background: Stunting has many long-term negative effects such as poor academic performances and low income. Stunted children are facing greater possibilities to grow into adults who are less educated, economically marginalised, less healthy and more susceptible to the non-communicable diseases. Therefore, the child is a predictor of poor quality of human resources, which further lowers the productive capability of a nation in the future. Gorontalo is a Regency of Gorontalo province which has a prevalence of nutritional status are short and very short on children aged 5 – 12 years with the percentage of 30.4%. This is above the cut-off point of stunting problems. Thus, stunting in Gorontalo can be classified as public health issues. Objectives:to investigate the relationship of family income, the energy intake and protein intake history with the nutritional status of school-aged children in the Gorontalo Regency.Methods: This research used quantitative methods approach with observational analytic study. Sample were 181 elementary school children. Assessment of nutritional status was done by anthropometry method based on height-for age index. The family income collected through direct interview on the parents. Consumption of energy and protein consumption were asked by the questionnaire survey. Bivariate analysis using chi-square to determine the relationship between variables and variables with variables bound.Results:The prevalence of school children suffering from stunting was 33.1%. Bivariate analysis results showed that the income of a family, a history of intake of energy and protein correlated significantly with stunting in school-aged children in Gorontalo Regency. Conclusion: Low family income is a risk factor for the occurrence of stunting on school-aged children in Gorontalo.